2007
DOI: 10.1111/j.1533-8525.2007.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

A Path Toward Interracial Marriage: Women's First Partners and Husbands across Racial Lines

Abstract: We examine interracial marriage as a culminating event in a sequence of intimate relationships across the life course. Using data from the 1995 National Survey of Family Growth, we analyze the background characteristics associated with selecting a first sex partner and first husband who differ in race/ethnicity from the respondent as well as the continuity across both outcomes. Our results show that respondents' race/ethnicity, parents' education, and region of birth are significant predictors of both choices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 67 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…While school integration policies in the 1960s sought primarily to increase achievement and self-esteem among African American children, in more recent decades, diverse schools have come to be seen as an important way to reduce social distance across racial and ethnic groups (Wells and Crain 1994). It is often hoped that, if young people go to school with peers from different racial and ethnic backgrounds, they will form close relationships across racial-ethnic boundaries and these relationships formed at young ages may set the stage for more close inter-racial-ethnic relationships throughout the life course (King and Bratter 2007, Wells and Crain 1994). Taking an optimistic view, having young people attend more diverse schools should help build a future U.S. society that is less fractured by race and ethnic divides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While school integration policies in the 1960s sought primarily to increase achievement and self-esteem among African American children, in more recent decades, diverse schools have come to be seen as an important way to reduce social distance across racial and ethnic groups (Wells and Crain 1994). It is often hoped that, if young people go to school with peers from different racial and ethnic backgrounds, they will form close relationships across racial-ethnic boundaries and these relationships formed at young ages may set the stage for more close inter-racial-ethnic relationships throughout the life course (King and Bratter 2007, Wells and Crain 1994). Taking an optimistic view, having young people attend more diverse schools should help build a future U.S. society that is less fractured by race and ethnic divides.…”
mentioning
confidence: 99%
“…Interracial romances in adolescence are correlated with interracial marriages in adulthood and may therefore pave the way for more multiracial households and children in the future (King and Bratter 2007). On the other hand, young people still make their relationship choices in a color conscious society shaped by legacies of slavery and legalized segregation, and recent changes that increase structural opportunities for inter-racial-ethnic dating may have very different meanings and lead to different behavioral responses across racial-ethnic and gender groups.…”
mentioning
confidence: 99%
“…Like interracial marriage, these other types of interracial relationships are indicators of the social barriers between racial groups, but they also may contribute to the erosion of these barriers by allowing individuals to learn about variation within racial groups and to question racial stereotypes (Kalmijn 1998). King and Bratter (2004) found that women are more likely to select husbands across racial lines if they select first sex partners across these lines. Finally, understanding other types of interracial relationships helps to enhance our understanding of interracial marriages.…”
mentioning
confidence: 99%
“…I control for highest level of parent education rather than respondent education because many respondents have not yet finished school by the time of their Wave 3 interview. Research indicates that parent education predicts involvement in interracial unions similarly to individual-level education, perhaps because individuals are influenced by their parents views on interracial unions (King and Bratter 2007). I use parent reports of their level of education but substitute the adolescent reports of their parents' education when the parent report is missing.…”
Section: Level 2 Variables: Individual Characteristicsmentioning
confidence: 98%